A non-canonical landscape of the microRNA system - Cipolla, Gabriel A. (Frontiers in Genetics, 2014)
Microribonucleic acids, best known as microRNAs or miRNAs, are small, non-coding RNAs with important regulatory roles in eukaryotic cells. Here, I present a broad review about highly relevant but generally non-depicted features of miRNAs, among which stand out the non-conventional miRNA seed sites, the unusual messenger RNA (mRNA) target regions, the non-canonical miRNA-guided mechanisms of gene expression regulation and the recently identified new class of miRNA ligands. Furthermore, I address the miRNA uncommon genomic location, transcription, and subcellular localization. Altogether, these unusual features and roles place the miRNA system as a very diverse, complex and intriguing biological mechanism.